Long‐term outcomes of catheter ablation in patients with longstanding persistent atrial fibrillation lasting less than 2 years. (24th September 2018) - Della Rocca, Domenico G.; Mohanty, Sanghamitra; Mohanty, Prasant; Trivedi, Chintan; Gianni, Carola; Al‐Ahmad, Amin; Burkhardt, J. David; Gallinghouse, G. Joseph; Hranitzky, Patrick; Sanchez, Javier E.; Horton, Rodney P.; Di Biase, Luigi; et al.
Abstract: Introduction: Outcome data after catheter ablation (CA) for longstanding persistent atrial fibrillation (LSPAF) lasting less than 2 years are limited and highly variable with different ablation approaches. We aimed to assess the long‐term outcomes in patients with LSPAF lasting less than 2 years undergoing extended pulmonary vein antrum isolation (PVAI) versus those with additional non‐pulmonary vein (PV) trigger ablation. Methods and Results: In this prospective analysis, 381 consecutive patients with LSPAF lasting less than 2 years (age: 64 ± 9 years, 76% male, atrial fibrillation duration: 19 ± 5 months) undergoing their first CA were classified into two groups: Group 1 ( n  = 104) received PVAI extended to PW plus isolation of superior vena cava (SVC) and Group 2 ( n  = 277) received PVAI + PW + SVC + non‐PV–trigger ablation. All patients were followed‐up for at least 2 years. In case of recurrence, repeat procedure was offered and non‐PV triggers were targeted for ablation in all. After a single procedure, 26 (25%) patients in Group 1 and 172 (62.1%) in Group 2 remained arrhythmia‐free ( P  < 0.001). A second procedure was performed in 58 of 78 (74.4%) patients in Group 1 and 77 of 105 (73.3%) patients in Group 2. Non‐PV triggers were identified in 52 (89.6%) and 54 (70.1%) patients in Groups 1 and 2, respectively, and targeted for ablation. Overall, 72 (69.2%) patients in Group 1 and 238 (86%) in Group 2 remained arrhythmia‐free ( P  < 0.001). Conclusion: In patients with LSPAF lasting less than 2 years, extended PVAI plus SVC isolation was less likely to achieve long‐term sinus rhythm. In the majority of patients, recurrence was due to non‐PV triggers and ablation of those resulted in better outcome.